Family Visitor Behavior Analysis at Cimory Dairyland on the Valley: a Sustainable Educational Tourism Study - MONICA, Monica; MARHENDI, Mengku (Journal of Tourism Economics and Policy, 2025)
This study analyzes family visitor behavior at Cimory Dairyland On The Valley in Semarang, focusing on visit motivations, behavioral patterns, and visitor satisfaction levels. Employing a qualitative approach with case study methodology, data were collected through in-depth interviews with 20 informants comprising family visitors, destination managers, and educational staff, supplemented by participant observation and document analysis. Results indicate that primary family visit motivations include seeking interactive educational experiences for children (78%), family recreation (65%), and nature interaction (54%). Visitor behavioral patterns demonstrate preferences for educational activities such as petting zoo and milk demonstration, with average visit duration of 4-5 hours. Visitor satisfaction reaches 82% with key factors including educational program quality, facility cleanliness, and staff friendliness. Challenges identified include capacity management during peak seasons, age-specific educational program diversification, and supporting infrastructure development. The study recommends strengthening sustainable educational programs, enhancing visitor management systems, and developing strategic partnerships with educational institutions to establish Dairyland as a premier family educational tourism destination in Central Java.